Effects of preemptive acupuncture on cognitive function of older patients after hip replacement: a randomized controlled trial - Tu, Qiguo; Zhou, Rong; Lv, Guiping; Wan, Zhengzuo; Chen, Shan; Que, Bin (Frontiers in Medicine, 2025)
BackgroundPostoperative cognitive impairment is a common complication in older patients after major orthopedic surgery; however, the underlying mechanism is not completely understood.ObjectiveThis study aimed to evaluate the effects of preemptive acupuncture on cognitive dysfunction after hip replacement and explore its potential mechanisms.MethodsFinally, 54 participants were randomized into sham acupuncture (n = 27) or acupuncture (n = 27) groups, who received acupuncture at the Sishencong (EX-HN1) and Baihui (DU20) acupoints, while participants in the sham acup group received sham acup at the target acupoints. Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) scores, the incidence of postoperative cognitive dysfunction (POCD), and other adverse events were assessed. The levels of microRNA (miR)-124 and miR-146a and inflammatory cytokines in the peripheral blood were detected. Correlations among miR-124, miR-146a, and inflammatory cytokines were analyzed.ResultsCompared with the sham acup group, the MMSE and MoCA scores in the acup group on the first and seventh day after surgery were higher, and the incidence of POCD on the first day was lower. Acupuncture upregulated levels of miR-124 and -146a and decreased the levels of TNF-α, IL-6, and IL-1β to protect cognitive function. Correlation analysis indicated that upregulated miR-124 and miR-146 were associated with lower levels of inflammatory cytokines.ConclusionAcupuncture protects postoperative cognitive function in older patients undergoing hip replacement, potentially reducing the incidence of POCD by upregulating miR-124 and miR-146a to inhibit neuroinflammation.Clinical trial registrationwww.chictr.org.cn, identifier ChiCTR2200062027.